Atmospheric formaldehyde at El Teide and Pic du Midi remote high-altitude sites. (1st August 2020) - Prados-Roman, Cristina; Fernández, Miguel; Gómez-Martín, Laura; Cuevas, Emilio; Gil-Ojeda, Manuel; Marusczak, Nicolas; Puentedura, Olga; Sonke, Jeroen E.; Saiz-Lopez, Alfonso
Abstract: Formaldehyde (CH2 O) is a tracer of the photochemical activity of the atmosphere. Linked to air quality, CH2 O is an ozone (O3 ) precursor and serves as a proxy for natural and anthropogenic reactive organic emissions. As a product of the photooxidation of methane (CH4 ) and other hydrocarbons (e.g., isoprene), CH2 O represents an important source of radicals in the remote free troposphere. This work aims at improving the characterization of this part of the troposphere where data are scarce. In particular, this study assesses the presence of CH2 O at two high-altitude remote sites: El Teide (TEI, 3570 m a.s.l., Tenerife, Canary Islands, Spain) and Pic du Midi (PDM, 2877 m a.s.l., French Pyrenees). Through ground-based remote sensing measurements performed during two field campaigns in July (TEI) and September (PDM) 2013, this study presents the vertical distribution of CH2 O at both locations. Results at PDM show that CH2 O mixing ratios follow a decreasing vertical profile with a mean maximum of 0.5 ± 0.2 nmol mol −1 (i.e., ppbv) at the instruments' altitude. At TEI, observations indicate an uplifted layer of CH2 O with a mean maximum of 1.3 ± 0.3 nmol mol −1 at 3.8 km a.s.l. (i.e., 300 m above the instrument's altitude). At both remote sites, the observed CH2 O levels are higher than expected for background methane oxidation (a threefold increase in the case of TEI). Air mass back trajectory analysis links CH2 O observations with abundant natural (e.g. forests) and/or anthropogenic isoprene emissions from the region nearby PDM, while the high CH2 O levels detected at TEI indicate in-plume formation of CH2 O resulting from its precursors emitted from west-African and Canadian fires. Finally, as a key trace gas for O3 and HOx chemistries, we estimate the upper limit of bromine monoxide (BrO) in the free troposphere at TEI and PDM to be 0.8 and 1.5 pmol mol −1 (i.e., pptv) respectively. Graphical abstract: Image 1 Highlights: Vertical profiles of formaldehyde mixing ratios at two high-altitude remote sites. Uplifted layer of formaldehyde above El Teide. Long-range transport of wildfire emissions into the North Atlantic free troposphere. Isoprene emissions from the Pyrenees and/or Spain reach Pic du Midi. First reported observations of atmospheric formaldehyde in the Pyrenees.